Ag/AgCl as an efficient plasmonic photocatalyst for greenhouse gaseous methane oxidation. Issue 6 (December 2021) - Wang, Fei; Liang, Xizhuang; Wang, Peng; Zhang, Qianqian; Tong, Fengxia; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Cheng, Hefeng; Dai, Ying; Huang, Baibiao
Abstract: In this work, quasi-cube Ag/AgCl plasmonic photocatalyst was synthesized by a simple co-precipitation method and in situ photo-reduction process. The synthesized Ag/AgCl shows high efficiency and good stability in the complete oxidation of nonpolar greenhouse gas methane under the simulated sunlight irradiation. Systematic experiments and finite-difference time-domain (FDTD) simulated calculations were employed to explore the reasons for the appreciable performance improvement, and results showed that the surface plasmonic resonance (SPR) effect of Ag nanoparticles can generate strong electric field which would induce the polarization of methane molecules, hence enhancing the adsorption of methane. This work provides a new idea for exploration of other plasmonic photocatalysts in the field of nonpolar gaseous molecules photo-oxidation. Graphical Abstract: The surface plasmonic resonance effect of Ag nanoparticles can generate a strong electric field to induce the polarization of methane molecules. Approximately no decrease in photocatalytic efficiency was observed even after recycling several times. ga1 Highlights: The Ag/AgCl plasmonic photocatalyst was used to degrade methane in gas phase. The Ag/AgCl exhibits high efficiency in the complete mineralization of methane. The SPR effect of Ag NPs can generate a strong electric field. The strong electric field can induce polarization of non-polar molecules.